1965
DOI: 10.1029/jz070i006p01311
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis of surfaces using alpha particles

Abstract: The chemical a n a l y s i s of s u r f a c e s u s i n g a l p h a p a r t i c l e i n t e r a c t i o n s h a s been i n v e s t i g a t e d . Simple i n s t r u m e n t s i n c o r p o r a t i n g Cm 242 a l p h a sources and semiconductor s i l i c o n d e t e c t o r s a r e d e s c r i b e d . The c h a r a c t e r i s t i c energy s p e c t r a of a l p h a p a r t i c l e s s c a t t e r e d a t l a r g e a n g l e s from t h i c k t a r g e t s of d i f f e r e n t elements have been d e t e r m i n e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1967
1967
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…Also, it enables one to compute the predicted α spectra for a sample with the composition determined from the X‐ray mode, assuming stoichiometric oxygen. This equation predicts intensities that are similar to those experimentally measured by Patterson et al [1965] and Economou et al [1970]. Economou et al [1970] and the current Pathfinder APXS alpha spectra find better matches to experimental data with a change in the power to which Z is raised from 0.5 to 0.6.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Also, it enables one to compute the predicted α spectra for a sample with the composition determined from the X‐ray mode, assuming stoichiometric oxygen. This equation predicts intensities that are similar to those experimentally measured by Patterson et al [1965] and Economou et al [1970]. Economou et al [1970] and the current Pathfinder APXS alpha spectra find better matches to experimental data with a change in the power to which Z is raised from 0.5 to 0.6.…”
Section: Introductionsupporting
confidence: 75%
“…The collected α back‐scattered intensity in a channel (therefore at a particular energy), theoretically predicted from the work of Rutherford et al [1930] and described by Patterson et al [1965] is in which x z is equal to the atom fraction of element z within the sample, I z is equal to the intensity of the pure sample element z for 100% abundance of each element measured from a standard sample of known chemical composition, and Z z is the atomic number of the element z within the sample. The denominator of is similar to a matrix correction for the intensity of the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A surface analysis performed by E. Franzgrote using the alpha-scattering technique[Patterson et al, 1965] indicated that the irradiated (darkened) side of the dunitc sample contained a readily detectable carbon content, whereas the unir-WEHNER, ef ol (1965,pp 6Comparison of photometric properties of basalt powder before and after hydrogenion irradiation by three investigators using different ion source systems. The best available evidence favors carbon as the principal contaminant.…”
mentioning
confidence: 99%
“…In order t o simplify the figure, data points have been omitted except in t h e m0re.i m porta n t reg ions of the spectra tered particles from the surface contaminant appear superimposed on the plateau from the substrate. A two-dimensional model 11. lustrating how the channeling phenomenon can be used t o locate foreign atoms in a crystal (9). I n the "random" case, the scattering from the small amount of oxygen and carbon atoms on the surface caniiot be resolved because of the large background from the substrate.…”
Section: Elastic Scattering In a Singlementioning
confidence: 99%